Implementasi Sistem Integrated-Mutasi (I-MUT) dalam Pengelolaan Mutasi ASN Berbasis Kapasitas Organisasi Digital: Indonesia - Benita Safitri; Asropi (LPPM STISIP IMAM BONJOL, 2026)
This study aims to analyse the implementation of the I-Mut system in the mutation management of the State Civil apparatus (ASN) and to identify factors that affect its success, particularly in terms of technology, organisational capacity, and digital governance. The study used a descriptive qualitative approach, with data collected through semi-structured interviews and document analysis. The study participants were six purposively selected individuals, comprising employees of the State Civil Service Agency (BKN), users of the I-Mut system in government agencies, and those who understand SPBE policy and ASN management. The results showed that implementing I-Mut can improve efficiency, transparency, and process simplification by digitising services. However, it has not run optimally due to limited human resource capacity, inconsistent system performance, and suboptimal data integration and interoperability across institutions. Therefore, this study recommends strengthening human resource capacity through continuous training, improving data integration and quality, and ensuring policy consistency to optimise the implementation of I-Mut in supporting the digital transformation of ASN management.